PEMANFAATAN NAUNGAN DAN MULSA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicium esculentum Mill.) - Abd. Syakur; Abd. Hadid; Dian Gustiani (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
This research was conducted in Bulupontu Dusun Jaya District. Sigi Biromaru, Sigi in January to April 2016. The purpose of this study was to examine the use of shade and mulch on the growth and yield of tomato plants. This research method is set in the design of this study using the draft petak Separated (Split Plot Design) with plots Main wil be attempted is the percentage of shade: N1 = 25% (Light received as much 75 %), N2 = 50 % (Light received as much 50 %), N3= (Light received as much 25 %), kids plot/ sub plot is mulching rice straw is composed of M0= Without mulch, M1= rice straw 1,9 kg/ plot, M2 =rice straw 3,8 kg/  plot, M3= rice straw 5,7 kg/ plot. The results of this study indicate that treatment interaction shade and mulch can give a real effecton plant height, fruit number and fruit weight. Total 78,11 cm high plant, obtained on the interaction of treatment 50% (N2) with mulch 5,7 kg/ plot (M3). While the highest number of fruits per plant fruit 16,55 on the interaction of treatmen 75 % (N3) with mulch 5,7 kg/ plot (M3). And total weight of the fruit per needs plots (kg) which showed the highest niali 1,28 kg on height 2 MST has th highest value on M1 ie 29,12 cm. percentage of shade does not significantly affect the growth and yield    of tomato. Key Words : Shade, Rice straw mulch, Tomato.